Student Behavior in Using Artificial Intelligence for Canva Instant Presentation - Raissa Ayuni Syahputri; Jaka Nugraha (Journal of Office Administration : Education and Practice, 2024)
This study aims to determine student behaviour in using artificial intelligence for Canva instant presentations. This study was conducted by students of the Office Administration Education study program, class of 2020, with a sample size of 250 from a population of 175 students determined using the Krejcie table with a significance level of 0.05. Data were analyzed using Structural Equation Modeling-Generalized Structured Component Analysis (SEM-GSCA) with the GSCA Pro application. The resulto f this study shows that perceived usefulness does not significantly influence attitude towards Canva. Perceived ease of use has a significant influence on attitude towards Canva. Innovativeness does not have a significant influence on attitude towards Canva. Perceived enjoyment has a significant influence on attitude towards Canva. Efficiency has a significant influence on attitude towards Canva. Attitude towards Canva has a significant influence on intention to use Canva. In conclusion, this study determines how AI in Canva instant presentations improves quality and efficiency and identifies factors influencing student behavior in its use.